2020
DOI: 10.1001/jamaoto.2020.2063
|View full text |Cite
|
Sign up to set email alerts
|

Using Intraoperative Recordings to Evaluate Surgical Technique and Performance in Mastoidectomy

Abstract: currently lack rigorous methods for assessing surgical skill and often rely on biased tools of evaluation.OBJECTIVES To evaluate which techniques used in mastoidectomy can serve as indicators of surgeon level (defined as the level of training) and whether these determinations of technique can be made based solely on the movement of the drill head or suction. DESIGN, SETTING, AND PARTICIPANTSIn this prospective, observational study conducted from January 1, 2015, to December 31, 2019, at a single tertiary care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…The study demonstrated reasonable metrics for evaluation of surgeon skill level including drill stroke count, drilling efficiency, stroke pattern and use of suction irrigator. As evaluation and assessment can be time consuming, this study also highlighted how short video segments can provide valuable information on skill level [20]. Another study also focused on intraoperative recording of mastoidectomies for assessment, found that using objective metrics were more accurate than subjective assessment in differentiating surgeon experience level.…”
Section: Intraoperative Video Recording In Otolaryngology Education: ...mentioning
confidence: 86%
“…The study demonstrated reasonable metrics for evaluation of surgeon skill level including drill stroke count, drilling efficiency, stroke pattern and use of suction irrigator. As evaluation and assessment can be time consuming, this study also highlighted how short video segments can provide valuable information on skill level [20]. Another study also focused on intraoperative recording of mastoidectomies for assessment, found that using objective metrics were more accurate than subjective assessment in differentiating surgeon experience level.…”
Section: Intraoperative Video Recording In Otolaryngology Education: ...mentioning
confidence: 86%
“…It is not surprising that mean drill speed increases with resident experience level, as similar findings have been reported in the studies of simulated and cadaveric mastoidectomies (14,17). These increases could be attributed to the increased confidence or efficiency a surgical resident obtains as they become more experienced in performing a mastoidectomy (18). When analyzing residents individually, all seven residents displayed increases in drill motion as they progressed through training.…”
Section: Discussionmentioning
confidence: 99%
“…Although one previous study demonstrated that some drill metrics subjectively assessed from video recordings by raters could be used to differentiate novice from experienced surgeons, the utility of SI metrics in differentiating surgeon experience level is less clear (18,20). In the current study, we observed that SI speed increased from the PGY2 to PGY4 level, then decreased to the PGY5 level.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Video-based evaluation has been used across different surgical fields to evaluate proficiency and has been useful in examining variability in technique, outcomes, and areas of improvement for surgeons and trainees. 3 , 4 , 5 , 6 For example, video review for bariatric surgeons demonstrated that better surgical skills were associated with lower 30-day postoperative complications, reoperation, readmission, and visits to emergency departments. 7 Similar studies with laparoscopic sleeve gastrectomy and pancreaticoduodenectomy have demonstrated an association between skill and outcomes.…”
Section: Introductionmentioning
confidence: 99%